The Effect of Size, Sales Growth, Current Ratio and Tattoo, on Company Value with ROE as a Mediating Variable (Study on Manufacturing Companies Listed on the Indonesia Stock Exchange in 2019-2021) - Widyakto, Adhi; Souisa, Johanis; Rachmawati, Windasari; Karim, Abdul (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
This study was conducted based on two things: First, the phenomenon that during 2019-2021 many manufacturing industry companies listed on the Indonesia Stock Exchange, have a Price Book Value (PBV) smaller than one. The question is why the phenomenon occurs. Second, several studies relating to the question produced different findings. The question arises about the determinants of PBV. Is PBV influenced by SIZE, Growth, Current Ratio, Tattoo and ROE. This research uses two kinds of theories, namely; signaling theory, Trade Off Theory Agency Theory. The data used is secondary data, which comes from the Financial Statements of Manufacturing Industry Companies listed in the Indonesia Capital Market Directory in 2018-2021. This study used panel data with a sample of 230 from 431 all manufacturing companies during 2019, 2020, 2021. Sampling based on purposive sampling. This study aims to find out the relationship between firm size, sales growth, current ratio, and total asset turnover on return on equity and firm value. Data analysis used multiple linear regression with the help of the smartPLS program. The results showed that firm size had no significant negative effect on return on equity. Sales growth, current ratio, and total asset turnover have no significant positive effect on return on equity. Firm size has no significant positive effect on book value. Sales growth, current ratio, and total asset turnover have no significant negative effect on book value. Return on equity has a significant positive effect on book value.